Case-resolving capacity of dental care of the unified health system: The perception of users in a city in the state of São Paulo, Brazil - Lima, Arinilson Moreira Chaves [UNESP]; Garbin, Cléa Adas Saliba [UNESP]; Corrente, José Eduardo [UNESP]; Saliba, Nemre Adas [UNESP]; Moimaz, Suzely Adas Saliba [UNESP] (FapUNIFESP (SciELO), 2018)
The aim of this study was to learn about the users’ perceptions concerning the case-resolving capacity of dental care in the Unified Health System and to analyze the associations between solving capacity and both sociodemographic characteristics and access to the service. This was a cross-sectional study with a quantitative approach, in which 461 users responded to individual interviews. The outcome variable was the case-resolving capacity of dental care, obtained through the question: “In your opinion, is the dentist of this health center managing to solve all your oral health problems (Yes/No)”. Independent variables were grouped into the following: sociodemographic and related to the access to the service. Most participants reported that their oral health problems were being solved. By using the Poisson regression, the lack of case-resolving capacity was found to be associated to the patients’ not considering the dental surgeon’s working hours convenient; to the long time they had to wait to get an appointment in the health center; and to the long time they had to wait in the waiting room. The results showed the positive view that users have about the case-resolving capacity of public dental care, and the relationship between access to the service and the said solving capacity.
Resolutividade do serviço odontológico no sistema único de saúde: A percepção de usuários de um município paulista, Brasil
Keywords: Dental care; Effectiveness; Health services accessibility; Unified health system